Astroglial Glutamine Synthetase and the Pathogenesis of Mesial Temporal Lobe Epilepsy - Sandhu, Mani Ratnesh S.; Gruenbaum, Benjamin F.; Gruenbaum, Shaun E.; Dhaher, Roni; Deshpande, Ketaki; Funaro, Melissa C.; Lee, Tih-Shih W.; Zaveri, Hitten P.; Eid, Tore (Frontiers in Neurology, 2021)
The enzyme glutamine synthetase (GS), also referred to as glutamate ammonia ligase, is abundant in astrocytes and catalyzes the conversion of ammonia and glutamate to glutamine. Deficiency or dysfunction of astrocytic GS in discrete brain regions have been associated with several types of epilepsy, including medically-intractable mesial temporal lobe epilepsy (MTLE), neocortical epilepsies, and glioblastoma-associated epilepsy. Moreover, experimental inhibition or deletion of GS in the entorhinal-hippocampal territory of laboratory animals causes an MTLE-like syndrome characterized by spontaneous, recurrent hippocampal-onset seizures, loss of hippocampal neurons, and in some cases comorbid depressive-like features. The goal of this review is to summarize and discuss the possible roles of astroglial GS in the pathogenesis of epilepsy.